Perencanaan Lansekap Desa Pertima sebagai Desa Wisata Berkelanjutan di Kecamatan Karangasem Kabupaten Karangasem - PUTRA, IWAN SEMARA; UTAMI, NI WAYAN FEBRIANA; SUGIANTHARA, ANAK AGUNG GEDE (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017, 2017)
Pertima Village is a village in the province of Bali which has 13 sub village and three indigenous villages which has potency to serve as a tourist village, so  it needs to be planned. Tourist villlage is a place which has certain characteristics and values that can be  special attraction for tourists with a special interest in rural life.  This study aims to determine some potencies and problems  which exist in the Pertima Village to develop this village as a tourist village by implementing concept of "Sustainable Tourism Village". The method used in this study were field survey with observation, interview, questionnaire and study literature technique. There were five stages conducted in this research such as  site preparation, inventory, analysis, synthesis and planning. The landscape planing were done by using the natural and culture resource approach.  Sustainable tourist village apllied was a tourist village that does not pollute or ruin the environment, economically profitable and socially acceptable.